The Effectiveness of TTW (Think-Talk-Write) Strategy in Teaching Writing Descriptive Text - Suminar, Ratna Prasasti; Putri, Giska (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2015)
This research entitled “The Effectiveness of TTW (Think-Talk-Write) Strategy in Teaching Writing Descriptive Text. TTW (Think-Talk-Write) strategy is one of strategy in teaching learning process, TTW (Think-Talk-Write) strategy one of cooperative learning. Think-Talk-Write (TTW) Strategy is starting from involvement of students in thinking or dialogue with it self after reading process. Then talk and share ideas (sharing) with friend before writing. One group consist of 4-6 students, in this group of students requested making notes, explaining, listening and sharing ideas with friends and express them through writing. The problem of the research is “To find out the effectiveness TTW (ThinkTalk-Write) strategy in teaching writing descriptive text?” The population in the research is the second grade students of UNSWAGATI CIREBON. The writer takes two classes of the second grade students as the sample from this research which were divided into two groups; experimental group (7AB) and control group (7CD). The instruments of collecting data are tests; pre-test and post-test. To analyze of data, the writer used a quasiexperimental design. The writer gave writing test to gather the data. There were pre-test and post-test. The formula that was used analyze the data was t-test. It was used to determine whether there was significance difference between students’ score in experimental group and control group.